2001
DOI: 10.1177/026765910101600211
|View full text |Cite
|
Sign up to set email alerts
|

Emergency redo mitral valve replacement in a 27-year-old pregnant female with a clotted prosthetic mitral valve, preoperative fetal demise and postoperative ventricular assist device: a case report

Abstract: A 27-year-old Laotian woman with a St Jude mechanical mitral valve became pregnant, requiring a change in her anticoagulant after the first trimester when her warfarin sodium (coumadin) was replaced with enoxaparin sodium (lovenox). Her prosthetic valve clotted and became dysfunctional. She was 16 weeks pregnant and was taken to the operating room for emergency surgery for replacement of the valve. The fetus had not been viable for 1-2 weeks, but still remained in utero. The clotted valve was replaced with ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…From these, we excluded 11 studies of 43 patients with artificial heart valves 20,23,36,47,52,54,55,65,72,74,91 ; 1 case report of primary pulmonary hypertension 49 ; 2 studies of 18 pregnancies in 16 patients 83 and 4 pregnancies 86 reported elsewhere; and 3 studies for methodologic reasons because insufficient information regarding LMWH use was given. 64,81,94 In total, 64 studies reporting 2777 pregnancies were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…From these, we excluded 11 studies of 43 patients with artificial heart valves 20,23,36,47,52,54,55,65,72,74,91 ; 1 case report of primary pulmonary hypertension 49 ; 2 studies of 18 pregnancies in 16 patients 83 and 4 pregnancies 86 reported elsewhere; and 3 studies for methodologic reasons because insufficient information regarding LMWH use was given. 64,81,94 In total, 64 studies reporting 2777 pregnancies were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical information is also available on the short-term use of lowmolecular-weight heparin for thromboprophylaxis in nonpregnant patients with prosthetic heart valves (32)(33)(34)(35). Published data on the use of low-molecularweight heparin in women with mechanical prosthetic heart valves during pregnancy are presently limited to small groups of patients (8)(9)(10)12,36,37) or to isolated reports (38)(39)(40)(41)(42)(43)(44), with several of these cases complicated by valve thrombosis (Table 1).…”
Section: Low-molecular-weight Heparinmentioning
confidence: 99%
“…Although this seemingly high incidence of thrombotic complications may raise a concern regarding the safety of low-molecular-weight heparin (46), it probably reflects a biased reporting of cases with complications. In addition, most of these cases have been associated with an inadequate dose, lack of monitoring, or subtherapeutic anti-Xa levels (10,36,38,(41)(42)(43). For example:…”
Section: Low-molecular-weight Heparinmentioning
confidence: 99%
“…Ten reports were found, of which 3 were small case series, 5 were case reports and two were prospective studies (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). One prospective, non-randomized clinical trial to evaluate the efficacy and safety of LWMH and two retrospective studies to identify an appropriate and safe anticoagulant regimen for pregnant women with prosthetic heart valves were included since they reported patients with prosthetic heart valves treated with LMWH during their pregnancy (22)(23)(24).…”
Section: Eligible Studiesmentioning
confidence: 99%